ANALISIS YURIDIS FORUM KEMITRAAN POLISI DAN MASYARAKAT DALAM PENYELESAIAN MASALAH MELALUI MUSYAWARAH BERDASARKAN SKEP KAPOLRI NO. : SKEP/737/X/2005 TENTANG KEBIJAKAN DAN STRATEGI KEPOLISIAN (Studi Kasus Polsek Bogor Utara) - San toso; Dadang Suprijatna; J. Jopie Gilalo (Fakultas Hukum Universitas Djuanda Bogor, 2016)
As a barometer of political stability, defense and security. Development of policy and strategy leadership of the Police on community policing (community policing) as a follow up of National Police chief SKEP No. Pol .: SKEP / 737 / X / 2005. The program is intended for the police closer to the community so that people are encouraged / motivated to cooperate with the police in assisting the principal task of the police to create security and order (security and public order). Identification of problems in this study were 1) How the duties and functions of the Police and Community Partnership Forum in resolving conflicts in society, 2) Any barriers and Efforts faced by Police and Community Partnership Forum in resolving conflicts in the community The purpose of this study was to determine the duties and functions FKPM, barriers, and efforts to resolve conflicts in society. In writing this essay, the writer used descriptive analytical research. This research method is used to make the description clear, systematic, transparent and precise about the facts / specific nature of the area and population which is then analyzed to obtain the desired facts. Results of this study concluded that the duties and functions of the Police and Community Partnership Forum in resolving conflicts in society in order to realize the maximum and community policing has not yet impact on the increasing public perception of the police. The direct impact of the policy community policing in all areas is simply the birth of the board-board FKPM. In terms of implementation, it appears less optimal competence of officers in the police station and police station level. Instructive culture within the police, which was adopted from the military norm policing policy making by officials on the ground is seen more as a mere 'implementation of new tasks' rather than the 'improvement of quality of service'.